Reclaimed wastewater as an ally to global freshwater sources: a PESTEL evaluation of the barriers - S. Gul; K. M. Gani; I. Govender; F. Bux (Aqua, 2021)
Together with climate change, rising living standards throughout the world have put pressure on existing freshwater sources and increased global water scarcity. The reclaimed wastewater projects face obstacles in sustainable implementation. This paper reviews Political, Economic, Social, Technological, Environmental and Legal (PESTEL) factors that act as barriers to the successful implementation of the reclaimed wastewater. Owing to COVID-19, pandemic and presence of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) in wastewater, future consequences on operations and public acceptance of reclaimed wastewater systems are discussed. This review will be useful for water experts, researchers and project planners for appropriate measures in future wastewater reuse projects. HIGHLIGHTS Public acceptance factors of reclaimed wastewater are reviewed by PESTEL analysis.; Mean acceptance rate for drinking application of reclaimed wastewater is lowest.; Contextualization of marketing message to the communities is necessary.; Identification of desired attributes can augment branding of reclaimed wastewater.;